2020
DOI: 10.1080/23288604.2020.1810921
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Common Understanding of Networks of Care through a Scoping Study

Abstract: The phrase "Networks of Care" seems familiar but remains poorly defined. A health system that exemplifies effective Networks of Care (NOC) purposefully and effectively interconnects service delivery touch points within a catchment area to fill critical service gaps and create continuity in patient care. To more fully elaborate the concept of Networks of Care, we conducted a multimethod scoping study that included a literature review, stakeholder interviews, and descriptive case studies from five low-and middle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 66 publications
1
63
0
2
Order By: Relevance
“…2 NOC is defined as "a group of … health service delivery sites deliberately interconnected through an administrative and clinical management model which promotes a structure and culture that prioritizes client-centered, effective, efficient operation and collaborative learning, enabling providers across all levels of care, not excluding the community, to work in teams and share responsibility for health outcomes." 11 The new NOC of CCBRT was comprised of government hospitals and catchment facilities operating across Dar es Salaam, originally started in 2010 with 8 facilities: 3 hospitals that were later upgraded to regional referral hospitals, and 5 health centers. In 2011 and again in 2013, additional health centers and 12 dispensaries, which are primary care sites with a limited scope of services (the level of facility down from health center in the Tanzanian health service delivery organizational structure), were added, to reach a total of 22 networked facilities.…”
Section: Overviewmentioning
confidence: 99%
“…2 NOC is defined as "a group of … health service delivery sites deliberately interconnected through an administrative and clinical management model which promotes a structure and culture that prioritizes client-centered, effective, efficient operation and collaborative learning, enabling providers across all levels of care, not excluding the community, to work in teams and share responsibility for health outcomes." 11 The new NOC of CCBRT was comprised of government hospitals and catchment facilities operating across Dar es Salaam, originally started in 2010 with 8 facilities: 3 hospitals that were later upgraded to regional referral hospitals, and 5 health centers. In 2011 and again in 2013, additional health centers and 12 dispensaries, which are primary care sites with a limited scope of services (the level of facility down from health center in the Tanzanian health service delivery organizational structure), were added, to reach a total of 22 networked facilities.…”
Section: Overviewmentioning
confidence: 99%
“…A NOC is defined as "a group of public and/or private sector service delivery sites deliberately interconnected through an administrative and clinical management model which promotes a structure and culture that prioritizes client-centered, effective, efficient operation and collaborative learning, enabling providers across all levels of care, not excluding the community, to work in teams and share responsibility for outcomes." 11 The NOC Framework proposes that the success of a NOC-as demonstrated by improved patient health outcomes in the targeted clinical areasis accomplished by attention to four interconnected domains: 1) Agreement and Enabling Environment, 2) Operational Standards, 3) Quality, Efficiency and Responsibility and 4) Learning and Adaptation. These case studies from Northern Nigeria and Lagos State use routinely reported data, program operational manuals, standard operating procedures (SOPs), and interviews with NOC stakeholders to retrospectively document the two NOC according to the NOC definition and framework.…”
Section: Introductionmentioning
confidence: 99%
“…12 The NOC approach, a style of integrated health delivery, is described in a multi-method scoping study and case studies from six diverse implementation settings. [1][2][3][4][5][6] The articles provide a set of practicable, measurable means to bridge Networks of Care and Universal Health Coverage.…”
mentioning
confidence: 99%
“…The NOC approach offers the possibility to learn from and improve subnational health management, financing and governance, including direct contracting to fill gaps in the public sector offerings. 1 The NOC approach is well suited to translating policies and guidelines into local-level implementation, managing delivery of essential health benefits packages, and providing accountable, trusted systems. 3,5 The use of NOC could improve quality, access, and equity while informing and advancing national pursuit of UHC goals, providing additional efficiencies in implementation, and strengthening the positions of Ministries of Health to leverage additional resources.…”
mentioning
confidence: 99%